Beliefs and strategies about urinary incontinence: a possible moderation role between symptoms and sexual function, and quality of life - Porto, Marta; Marôco, João; Mascarenhas, Teresa; Pimenta, Filipa (Frontiers in Psychology, 2023)
Background: Urinary Incontinence (UI) has numerous repercussions in women´s lives, and it is underreported/underdiagnosed.Objective: The present study aimed to understand: 1) the differences between women with and without urine loss regarding Quality of Life (QoL) and Sexual Function (SF); 2) the possible moderation role of UI-related beliefs and strategies on the relationship between UI-symptom severity and SF and QoL, in women with UI.Methods: Cross-sectional Design. Participants: Primary aim: Overall, 2,578 women aged 40-65 (Mage=49.94, DPage=6.76) were collected online. Secondary aim: 1,538 women who self-reported having urine loss occasionally/frequently (Mage=50.19, DPage=6.58). All data analyses were done with IBM SPSS Statistics and R statistical system 4.0 (R Core Team, 2020) through RStudio.Statistical Path analysis was performed with the lavaan package to study the hypothetical association and moderating effects between the variables.Results: Primary aim: women without UI had a better SF (t(2576)=3.13, p = .002; 95% C.I., .18 to .80) and QoL (t(2576)=7.71, p < .001; 95% C.I., 3.14 to 5.28) than their counterparts with UI.Secondary aim: UI-related coping strategies attenuated the impact of UI-symptom severity on SF(β =-.07; p=0.041); the more dysfunctional the UI-related beliefs were, the poorer QoL was (β= -.06; p=0.031); the more frequent the UI-related hiding/defensive strategies were, the poorer QoL was (β=-.26; p<.001).Discussion: Limitations: online data collection, which thwarted the clarification of participants, if needed; absence of a UI medical diagnosis (only self-reported measures were used). Strengths and practical implications: i) the crucial role of UI-related beliefs and strategies in the QoL of women with UI; ii) the impact that UI-concealing/defensive strategies have in attenuating the impact of UI-symptom severity on SF, which might be perceived as a short-term benefit and hence contribute to maintaining the UI condition and constitute a barrier to help-seeking, iii) impact of UI-symptom severity on QoL and SF (including a comparison group entailing women without UI, which is scarcely used); and iv) the use of gold-standard and psychometrically robust instruments.Changing dysfunctional UI-related beliefs and strategies in clinical settings may improve the QoL; UI-concealing strategies may reinforce themselves by immediate effects on SF, but are not functional in the long term.